PERAN GAYA KOMUNIKASI TERHADAP MOTIVASI PADA INDUSTRI MANUFAKTUR OTOMOTIF DI KOTA TANGERANG - Joni Prihatin; Uli Wildan Nuryanto; Prof. Muhammad Suparmoko (National Conference on Applied Business, Education, & Technology (NCABET), 2021)
The Automotive sector industry has grown rapidly since 1970 had a positive impact on the country’s economy which are high GDP contribution and being able to become a job field for 350 thousand of direct workers and 1,2 million of indirect workers. Therefore, this sector needs to be supported do that continues advance and develop. One of this way by management of human resources to increasingly the work motivation of its workers where this variable influenced by many things, one of which is communication style. This research was conducted using a quantitative approach using survey methods and causality design with SEM PLS data analysis techniques. The sample used 160 respondents with the number of 6 hypothesis tested. The result obtained from two variables there are 3 indicators that are not since to the loading factor < 0,70 so those indicators excluded from the model. For the result of second model analysis, inner model analysis and blindfolding analysis of the 2nd model, there was found that all parameters were in accordance with the requirements. The hypothesis result shows that all hypothesis tested were accepted. Communication style has a signification effect on work motivation with the magnitude 51,1% while the remaining of 48,9% influenced by others variable outside the model being tested.